ANALISIS PRODUK KREATIVITAS SENI KOLASE PADA SISWA KELAS V SD NEGERI 1 MONTONGSARI - Nur Fadhilatul Rifkia; Prasena Arisyanto; Riris Setyo Sundari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims enhace collage activities for grade students and foater environmental awareness. This study analyzes creative collage products by fifth-grade students at SD Negeri 1 Montongsari using plastic waste and seeds. A interviews with teachers and students, and documentation of the collage results. The results showed that students were able to express ideas, color combinations, and pasting teachniques. The students collage reflected novelty in material selection, for exsample, the use of plastic waste, originality in individual style, and benefist in developing fine motor skills, self confidence, and environmental awareness.